Evaluation of near-isogenic lines of rice introgressed with submergence tolerance and deep rooting at early growth stage - Soe, Ibrahim; Hang, Nguyen Thi Thu; Odama, Emmanuel; Chepkoech, Rael; Ookawa, Taiichiro; Ismail, Abdelbagi M.; Sakagami, Jun-Ichi (Springer, 2025)
Rice varieties that minimise shoot elongation under submergence and provide tolerance for up to two weeks carry SUB1A. Conversely, DRO1 responsible for deep-rooting, helps in water and nutrient acquisition under drought. In this study, we compared the growth of NIL-SUB1, NIL-DRO1, and NIL-SUB1DRO1 with IR64 background for its dual tolerance to submergence, drought, and recovery. Submergence was on 14- and 16-days old seedling for 7 and 10 days and allowed to recover for 7 and 10 days respectively. Drought was also imposed on 14- and 13-days old seedlings for 18 and 29 days followed by 10 days recovery respectively. Submergence and drought adversely affected growth and performance of the genotypes. Compared to IR64, NIL-SUB1DRO1 suppressed shoot elongation during flooding, maintained the function of the leaf photosystem, and under drought conditions, maintained leaf water potential and contributed to increased dry matter weight of shoots and roots. In addition, NIL-SUB1DRO1 exhibited deep rooting, with roots extending into the lower subsurface layers under drought condition. It is suggested that NIL-SUB1 showed potential tolerance to submergence and NIL-DRO1 to drought. Furthermore, NIL-SUB1DRO1 was found to be tolerant to both drought and flooding.